Mitogenome characterization and phylogeny of Huzhu white yak (Bos grunniens) in China. Issue 6 (3rd June 2022) - Luo, Jing; Li, Guangzhen; Li, Ruizhe; Yang, Yongqing; He, Decang; Liu, Wenxian; Yosri, Mohammed; Ma, Zhijie
Abstract: White yak is a unique and precious economic livestock animal in the world. In this study, the mitogenome of Huzhu white yak was firstly sequenced using Illumina high-throughput sequencing technique and then the assembly was annotated. We also explored mitogenome characterization and phylogeny of Huzhu white yak. Our results showed that the mitogenome of Huzhu white yak is a circular molecule with 16, 323bp length including a non-coding control region (D-loop), two ribosomal RNA genes ( 12S rRNA and 16S rRNA ), 22 transfer RNA genes and 13 protein-coding genes. The contents of four nucleotides (A, G, C and T) were 33.71%, 13.21%, 25.80%, and 27.28%, respectively, yielding a lower GC content (39.01%) than AT (60.99%). Phylogenetic analysis suggested that Huzhu white yak possessed the closest relationships with Huanhu, Jiulong, Datong, Jinchuan, Sibu, Ashdan and Pali yak breeds, and closer to wild yak and Bazhou breed.